User experiences and perceptions of health wearables: an exploratory study in Cambodia - Marco Liverani; Por Ir; Virginia Wiseman; Pablo Perel (BMC, 2021)
Abstract Background In many low- and middle-income countries (LMICs), health system capacities to address the burden of non-communicable diseases (NCDs) are often inadequate. In these countries, wearable health technologies such as smartbands and smartwatches could be used as part of public health programmes to improve the monitoring, prevention, and control of NCDs. Considering this potential, the purpose of this study was to explore user experiences and perceptions of a health wearable in Cambodia. Methods Data collection involved a survey, conducted between November 2019 and January 2020, among different categories of participants (including hypertensive participants, non-hypertensive participants, postgraduate students, and civil servants). All participants were given a sample of a watch-type wearable and advised to use it day and night. One month after product delivery, we conducted a survey to explore their views and experiences. Results were analysed by using descriptive statistics and Chi square or Fisher's exact test to compare responses from urban and rural participants. Results A total of 156 adult participants completed the study. Technology acceptance was positive overall. 89.1% of the participants said they would continue using the watch and 76.9% of them would recommend it to either friends or relatives, while 94% said the device stimulated them to think more frequently about their health. However, challenges to technology adoption were also identified, including concerns with the accuracy and quality of the device and unfamiliarity with the concept of health self-monitoring, especially among the elderly. Short battery life and cost were also identified as potential barriers to continued use. Conclusions Health wearables are a promising new technology that could be used in Cambodia and in other LMICs to strengthen health sector responses to the challenges of NCDs. However, this technology should be carefully adapted to the local context and the needs of less resourced population groups. In addition, further studies should examine if adequate health sector support and infrastructure are in place to implement and sustain the technology.